2014
DOI: 10.1038/npp.2014.209
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Changes in Conflict Monitoring and Error Detection as Predictors of Alcohol Use in Late Adolescence

Abstract: Adolescence is a vulnerable period for the development of substance use and related problems. Understanding how exposure to drugs influences the adolescent brain could reveal mechanisms underlying risk for addiction later in life. In the current study, 87 adolescents (16-20-year olds; the local legal drinking age was16, allowing the inclusion of younger subjects than usually possible) underwent EEG measurements during a Go/No-Go task with and without alcohol cues; after placebo and a low dose of alcohol (0.45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…The current study did not directly compare performance on the CST to the SST and the Go/NoGo task. However, our results fit well with a rich literature suggesting that acute alcohol exposure spares attentional inhibition, while response inhibition is impaired (de Wit et al 2000;Marczinski et al 2005;Loeber and Duka 2009;Marinkovic et al 2012;Gan et al 2014;Korucuoglu et al 2015;Stock et al 2016). Such a selective effect of acute alcohol on behavior was observed when response and attentional inhibition were examined in the same sample (Bartholow et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The current study did not directly compare performance on the CST to the SST and the Go/NoGo task. However, our results fit well with a rich literature suggesting that acute alcohol exposure spares attentional inhibition, while response inhibition is impaired (de Wit et al 2000;Marczinski et al 2005;Loeber and Duka 2009;Marinkovic et al 2012;Gan et al 2014;Korucuoglu et al 2015;Stock et al 2016). Such a selective effect of acute alcohol on behavior was observed when response and attentional inhibition were examined in the same sample (Bartholow et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“… 31 or Mäki-Marttunen 33 have shown a lower N2 amplitude responding to both go and no-go trials in patients with mild brain damage affecting cognitive control. These differences at brain level are also supported by behavioural studies showing that poorer performance on no-go trials is often accompanied by poor performance on go trials (for example in gamblers 35 , smokers 36 , 37 , adults with attention deficit hyperactivity disorder 38 , or adolescents facing alcohol cues 39 ). The N2 component on go trials has usually been associated with allocation of resources to the detection and categorization of the target stimulus, and its evaluation and comparison in working memory 30 , 31 , 34 .…”
Section: Discussionmentioning
confidence: 74%
“…The absence of an effect on the N2 after cocaine and cannabis suggests that neither pre-motor response inhibition processes, nor conflict monitoring, is altered by the drug. Interestingly, earlier acute administration studies with alcohol and cannabinoids also showed that the N2 amplitude (when measured in a neutral task condition) was unaffected (Theunissen et al 2012;Korucuoglu, Gladwin & Wiers 2014;Stock et al 2014). This suggests that across several classes of drugs of abuse, effects on response inhibition might be selective to a later, evaluative stage of response inhibition, while leaving pre-motor inhibition/conflict processing intact.…”
Section: Discussionmentioning
confidence: 82%